Tourism and hospitality : issues and developments - Seba, Jaime A. (Apple Academic Press, 2012)
"Tourism has become a key global economic activity as expectations with regard to our use of leisure time have evolved, attributing greater meaning to our free time. Tourism is one of the world's largest industries, and in many regions it is the single largest source of investment and employment. This new book provides a look at many important issues in the field of tourism and hospitality, including understanding tourist preference, satisfaction, and motivation; tourism and hospitality education; rural tourism and its impact on local residents; the increasing popularity of cultural and heritage tourism; strategies for sustainable tourism; and more"